Numerical study of downwash flow on rice plant protection drone with computational fluid dynamics method - Mohamad Yamin; Muhammad Zidan Alfasha (Jurnal Polimesin, 2024)
Unnamed Unmanned Aerial Vehicles (UAVs) are increasingly being utilized in various industries, including agriculture, to support the growing demand for food. UAVs streamline work processes and are particularly useful in the spraying method for plant protection. This study aims to analyze the characteristics of the downwash flow, which are influenced by factors such as flight altitude, airfoil profile, and the flying speed of the drone. Unlike previous studies that used 6-blade UAVs, this research focused on a 4-blade configuration. The study employed Computational Fluid Dynamics (CFD) to analyze drone geometry and input boundary conditions based on environmental factors. The drone's flying altitude significantly impacted downwash flow, particularly concerning In Ground Effect (IGE) and Out of Ground Effect (OGE) conditions. Unlike previous research, this study considered the airfoil profile of the propeller, which, along with the drag and lift coefficients from the airfoil geometry, affected the downwash flow. The drone's flying speed, related to the relative wind speed around its working area, also influenced pressure distribution and downwash flow speed. These factors significantly impacted downwash flow and determined the distribution of plant protection droplets on the rice field. The results indicated that increasing flight altitude reduced the ground effect, affecting the quadcopter's downwash. Similarly, flight speed had a similar effect on downwash as altitude. Based on these findings, the study recommended a flight altitude of 2 m and a speed of 2 m/s for optimal downwash and proper distribution of plant protection.